A Website Based Information System on Startup SharingKu - Kristiani Br Munthe; I Made Sukarsa; I Made Sunia Raharja; Ni Wayan Wisswani (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2022)
Mental health is one of the health problems that many people experience. Consultation or therapy is an alternative that can be done when mental conditions are bad. Based on interviews that have been conducted with several users in conducting consultations, there are several obstacles in conducting direct consultations with psychologists. The obstacles experienced consisted of several things such as PPKM regulations, personal anxiety to have direct contact with other people, the difficulty of arranging schedules for two parties, administrative matters and many more. This is certainly not effective in terms of time, cost and effort. The difficulties experienced by the user stimulate an innovation in creating a Website-Based Information System for the ShaingKu Startup. The purpose of this development is to design an information system that makes it easier for various groups, especially patient users, to be able to conduct online consultations more easily and effectively both in time, cost and effort. The final result of this research is a system that can be implemented and has passed the trial process that has been successful. The test consists of the functionality of a patient user who has successfully placed an order, a psychologist user who has successfully managed patient data, an admin user who has successfully managed psychologist data and a super admin user who has successfully registered psychologist and admin accounts.